In vitro dynamic degradation behavior of new magnesium alloy for orthopedic applications. Issue 4 (13th August 2014) - Yang, Gui‐Fu; Kim, Yu‐Chan; Han, Hyung‐Seop; Lee, Gwang‐Chul; Seok, Hyun‐Kwang; Lee, Jae‐Chul
Abstract: We report on methodologies for use in the design of a biodegradable Mg alloy appropriate for load‐bearing but temporary orthopedic implant applications. Comparative studies of Mg‐5Ca and Mg‐5Ca‐1Zn were conducted to explore the effects of a combination of minor alloying and hot extrusion, on the alloy's mechanical properties and corrosion resistance. The extruded Mg‐5Ca‐1Zn exhibited high ultimate compressive strength of 385 MPa and suffered no significant structural degradation even after immersion in simulated body fluid for 30 days. Mg‐5Ca‐1Zn alloy showed the mechanical strength and controlled corrosion rate to be considered as an ideal candidate for biodegradable orthopedic implant material. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 807–815, 2015.